2015
DOI: 10.1111/ecno.12033
|View full text |Cite
|
Sign up to set email alerts
|

The Risk–Return Binomial After Rating Changes

Abstract: Risk-averse investors take into consideration risk-return tradeoff for decide their new position after the release of relevant information. This paper analyzes the informational content of rating change announcements focusing on the joint reaction they cause on the risk-return binomial. Our purpose is to identify the main factors that signal which announcements are informative. To do that we estimate a binomial logit model for the probability of informative content of credit rating announcements.We analyze a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Weinstein (1977), however, concludes that bond returns are not related to rating changes in a period of up to 6 months after the announcements. Later, other authors have identified links between rating announcements and issuance spread (e.g., Iannotta, Nocera, & Resti, 2013) and return (e.g., Abad & Robles, 2015;Liu & Thakor, 1984;Stover, 1991).…”
Section: Credit Ratings and Financial Instruments' Performancementioning
confidence: 99%
“…Weinstein (1977), however, concludes that bond returns are not related to rating changes in a period of up to 6 months after the announcements. Later, other authors have identified links between rating announcements and issuance spread (e.g., Iannotta, Nocera, & Resti, 2013) and return (e.g., Abad & Robles, 2015;Liu & Thakor, 1984;Stover, 1991).…”
Section: Credit Ratings and Financial Instruments' Performancementioning
confidence: 99%
“…Looking at the South African investment status, this is a low number, although the issue could be because of high unemployment figures. Most of the elderly people above 60 years old live primarily on social grants (Abad & Robles, 2015). However, Karimli et al (2014, p. 661) mentioned that policy makers have recently been calling for the acceleration of savings accounts as a tool to empower those who are poverty stricken.…”
Section: Investment and Savingsmentioning
confidence: 99%